Empower parents, enable breastfeeding: a behavioral change communication exercise conducted at a community health centre of Haryana - Gandhi Periyasamy, Aravind; Dalui, Nairita; Aggarwal, Arun K.; Goyal, Sanjeev; Jain, Rupa (International Journal Of Community Medicine And Public Health, 2019)
In India, only 41.6% of the children are breastfed within 1 hour and 54.9% of the children are exclusively breastfed till 6 months. In order to promote breastfeeding, the first week of August is being observed as World Breastfeeding week. We organized a brainstorming session followed by an Interactive, audio-visual health education event on breastfeeding for the pregnant women and their household members at a Community Health Centre (CHC) in Haryana, during that week. A behavior change communication (BCC) session was held on 1st August 2019 at the Antenatal clinic of the CHC. Target population was the pregnant, lactating mothers and their household members. Needs assessment was done to assess their current knowledge, attitude and needs about the breastfeeding and breast milk, by interacting with them and posing questions. Based on the above needs assessment exercise, we delivered a health education session. The household members were enlightened about their role in breastfeeding. The behavior change communication exercise, tailored to local population and conducted by us would have improved the knowledge, attitude of the pregnant women and their family members towards breastfeeding, and in turn will improve the practice in near future. The exercise is replicable in other settings, by tailoring it according to the local needs.